Rationality and the reflective mind - Stanovich, Keith E., 1950- (New York ; Oxford : Oxford University Press, 2011)
The author attempts to resolve the debate about how much irrationality to ascribe to human cognition. He shows how the insights of dual-process theory and evolutionary psychology can be combined to explain why humans are sometimes irrational even though they possess cognitive machinery of remarkable adaptiveness.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Reasoning (Psychology); Individual differences; Intellect; Cognition